Hyperglycemia, diabetes and stroke: Focus on the cerebrovasculature - Ergul, Adviye; Li, Weiguo; Elgebaly, Mostafa M.; Bruno, Askiel; Fagan, Susan C. (Vascular pharmacology, 2009)
Acute ischemic stroke (AIS) results from the occlusion of an artery and causes vascular and neuronal damage, both of which affect the extent of ischemic injury and stroke outcome. Despite extensive efforts, there is only one effective treatment for AIS. Given that up to 40% of the AIS patients present with admission hyperglycemia either as a result of diabetes or acute stress response, targets for neuronal and vascular protection under hyperglycemic conditions need to be better defined. Here, we review the impact of diabetes and acute hyperglycemia on experimental stroke with an emphasis on cerebrovasculature structure and function. The relevance to clinical evidence is also discussed.